Arbitrators as a Legal Profession in The Alternative Role of Dispute Resolution in Indonesia - Muhammad Iqbal Baiquni (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2022)
The profession of arbitrator in Indonesia is a profession that has bright prospects for the present and the future. Based on Article 1 point 7 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, the arbitrator profession is one or more persons who are chosen by the parties to the dispute or appointed by the District Court or by the arbitration institution, to give a decision regarding a particular dispute. which has been resolved by arbitration. An absolute requirement for an arbitrator is a professional, this is closely related to the ethics of the legal profession in carrying out its duties and authorities. The professional position of the Arbitrator is as a private party who is given rights and obligations, authorities and responsibilities by the state (AAPS Law No. 30 of 1999). In this paper, the author uses the juridical-normative method with a statute approximation approach or a study of legislation. This paper reviews more deeply about the Arbitrator Profession within the scope of the Legal Profession. Profesi Arbiter di Indonesia menjadi profesi yang mempunyai prospek cerah untuk masa sekarang hingga masa mendatang. Berdasarkan Pasal 1 angka 7 UU No.30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa, profesi arbiter merupakan seorang atau lebih yang lebih yang dipilih oleh para pihak yang bersengketa atau yang ditunjuk oleh Pengadilan Negeri atau oleh lembaga arbitrase, untuk memberikan putusan mengenai sengketa tertentu yang diserahkan penyelesaiannya melalui arbitrase. Syarat mutlak dimiliki seorang arbiter adalah profesional, hal ini berkaitan erat dalam etika profesi hukum dalam melaksanakan tugas dan wewenangnya. Kedudukan profesi Arbiter adalah sebagai pihak swasta yang diberikan hak dan kewajiban, wewenang dan tanggung jawab oleh negara (UU AAPS). Dalam tulisan ini penulis menggunakan metode yuridis-normatif dengan pendekatan statute approch atau studi perundang-undangan. Tulisan ini mengulas lebih dalam tentang Profesi Arbiter dalam ruang lingkup Profesi Hukum.